2015
DOI: 10.3389/fbioe.2015.00175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porosity of Alumina and Zirconia Ceramics toward Pre-Osteoblast Response

Abstract: It is acknowledged that cellular responses are highly affected by biomaterial porosity. The investigation of this effect is important for the development of implanted biomaterials that integrate with bone tissue. Zirconia and alumina ceramics exhibit outstanding mechanical properties and are among the most popular implant materials used in orthopedics, but few data exist regarding the effect of porosity on cellular responses to these materials. The present study investigates the effect of porosity on the attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
3
24
0
4
Order By: Relevance
“…In fact, the roughness values were influenced by many factors such as the process of surface preparation, the presence of porosity, and cracks distribution within the coating. Based on the fact that the living cell tissue favoured the porosity between 1-10 µm [26], the present result suggests that the surface roughness of YSZ/TiO2 coatings may improve the osteoblasts attachment as well as promote a good osseointegration.…”
Section: Roughnessmentioning
confidence: 64%
See 1 more Smart Citation
“…In fact, the roughness values were influenced by many factors such as the process of surface preparation, the presence of porosity, and cracks distribution within the coating. Based on the fact that the living cell tissue favoured the porosity between 1-10 µm [26], the present result suggests that the surface roughness of YSZ/TiO2 coatings may improve the osteoblasts attachment as well as promote a good osseointegration.…”
Section: Roughnessmentioning
confidence: 64%
“…The YZP/TiO2 coating exhibited a relatively less wettability but this surface was proper from the point of morphology. Previous studies [26,27] claimed that a good osseointegration requires a proper surface topography with micropores with high surface roughness to support the cell attachment. This suggests that instead of low wettability, the YZP/TiO2 ceramic coating demonstrated high roughness value, thus, beneficial for cell growth and attachment [16,18].…”
Section: Wettabilitymentioning
confidence: 99%
“…It appears that the chemical composition of the ceramics did not affect the cell viability and proliferation, demonstrating the capacity of magnesia ceramics to support cell growth either in combination with zirconia or as pure magnesia. Previous studies have reported on the positive effect of scaffold porosity on cell proliferation, including zirconia and alumina ceramics [ 25 ]. In this study, the porosity of the ceramics ranging from 30–37% was not found to affect the cell viability, proliferation and osteogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy in the published literature as to the effect of porosity on bone regeneration. Although it has been generally recognized that large pores (>100 µm) enhance new bone formation because they allow the migration and proliferation of osteoblasts and mesenchymal cells, it has also been reported that presence of micro-porosity alters the pattern and dynamics of osteointegration [ 26 ], and might enhance ionic exchange with body fluids. It has also been reported that a nanoporous structure improves cell adhesion, proliferation, and differentiation.…”
Section: Discussionmentioning
confidence: 99%